Identifying color morphotypes of the species Leptodius exaratus (Brachyuran: Xanthidae) based on the molecular and electron microscopy studies - F Chenari; S.M.B Nabavi; M.A. Salari; A Savari; H Zolgharnein (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
According to morphological studies, Leptodius exaratus is one of the most common brachyuran species and the only known species of this genus which have been found in intertidal rocky shores along the Persian Gulf coast. Since the existence of hidden species among the crustacean species are very common, the aim of this study is to investigate the probability of hidden species identification among eight color morphotypes that were identified as Leptodius exaratus species in morphological studies. For this purpose, eight color morphotypes of Leptodius exaratus species were collected from rocky shores of Bushehr province. Then, the first male gonopods were separated and photographed by Scanning Electron Microscopy (SEM). For conducting molecular studies, DNA was extracted with a phenol-chloroform mixture and mitochondrial Cytochrome Oxidase subunit I (COI) gene was amplified and sequenced. The results showed that mitochondrial COI nucleotide sequences were not identical in all color morphotypes. These results were reflected in topology of evolutionary trees for both analyses (maximum likelihood, bayesian). Studying the ultrastructure of the apical segments of the first male gonopods showed fundamental differences in the apical organs of some color morphotypes. These results indicated that all samples did not belong to a single species and there were hidden species among them. Molecular evidence also showed that mitochondrial COI nucleotide sequences of eight color morphotypes of Leptodius exaratus from the Persian Gulf and the registered sequence of such species from Indonesia were in separate clusters. Identification based on the morphology of the first male gonopods using scanning electron microscopy (SEM) and the COI gene were useful research methods in the present study.